Legal Certainty Against the Annulment of Ultra Petita Divorce Decisions (Case Study of Decision Number 132/Pdt. G/2019/PN Bpp Jo Decision Number 125/Pdt/2019/PT.SMR): Kepastian Hukum terhadap Pembatalan Putusan Perceraian yang Bersifat Ultra Petita (Studi Kasus Putusan Nomor 132/Pdt. G/2019/PN Bpp Jo Putusan Nomor 125/Pdt/2019/PT.SMR) - Andi Nadyafatin Wadianita; Mustakim (PT Syamilah Literasi Islami, 2024)
Article 24 of the 1945 Constitution of the Republic of Indonesia in conjunction with Article 1 paragraph 1 of Law Number 48 of 2009 concerning Judicial Power regulates the authority of court judges who have the freedom to make decisions to the extent regulated by law. However, civil court judges are prohibited from committing ultra petita which can result in the annulment of the decision at the appeal level as happened in Decision Number 125/Pdt/2019/PT.SMR. The problem in this study is how are the criteria for ultra petita court decisions? How are the decisions and legal considerations of the judges of the East Kalimantan High Court Decision Number 125/Pdt/2019/PT.SMR which annulled the Balikpapan District Court Decision Number 132/Pdt.G/2019/PN.Bpp on divorce considered as ultra petita? This research method is normative juridical using secondary data. The results of the research state that the criteria for ultra petita court decisions are first the judge's decision that exceeds the petitum; Second is that the Court Judge who grants part of the prima facie petitum and part of the subsidiary petitum; Third is that the Court Judge is active. The decision and legal reasoning of the Judge of the East Kalimantan High Court Number 125/Pdt/2019/PT.SMR which annulled the decision of the Balikpapan District Court Number 132/Pdt.G/2019/PN.Bpp on divorce is considered as ultra petita is not appropriate. This is because the Judge of Balikpapan District Court gave a clear and detailed reason in his consideration, namely in the context of orderly administration. Other than that, there is a request for ex aequo et bono from the plaintiff. Another thing is the freedom of judges in deciding cases as mandated by the Constitution.